Promiscuous Gene Expression in the Thymus: A Matter of Epigenetics, miRNA, and More? - Ucar, Olga; Rattay, Kristin (Frontiers in Immunology, 2015)
The induction of central tolerance in the course of T cell development crucially depends on promiscuous gene expression (pGE) in medullary thymic epithelial cells (mTECs). mTECs express a genome-wide variety of tissue restricted antigens (TRAs), preventing the escape of autoreactive T cells to the periphery and the development of severe autoimmunity. Most of our knowledge of how pGE is controlled comes from studies on the Autoimmune Regulator (Aire). Aire activates the expression of a large subset of TRAs by interacting with the general transcriptional machinery and promoting transcript elongation. However, further factors regulating Aire-independent TRAs must be at play. Recent studies demonstrated that pGE in general and the function of Aire in particular are controlled by epigenetic and post-transcriptional mechanisms. This mini-review summarizes current knowledge of the regulation of pGE by miRNA and epigenetic regulatory mechanisms such as DNA methylation, histone modifications, and chromosomal topology.